Applying Quantitative Appraisal Analysis to the Study of Institutional Discourse: The Case of EU Migration Documents - Mira Tupala (SpringerOpen, 2022)
This article addresses the methodological issues related to applying the appraisal framework quantitatively with a corpus of institutional texts. The aim is to explore how to best annotate evaluative expressions in official institutional documents which are usually considered as factual and formal rather than attitudinal and affectual. Using a corpus of migration documents of the European Union as a point of reference, I outline a way of analysis in which each case of appraisal is systematically accounted for and annotated accurately with regard to the socio-cultural context of the EU, serving to deepen and widen the scope of the appraisal analysis. Ultimately, the study of evaluative patterns used in institutional discourse can reveal the ways in which evaluation is integrated into the structures of formal institutional language and how evaluation towards different phenomena (e.g. migration) is constructed.